Sosialisasi Strategi Pemanfaatan Media Sosial Untuk Meningkatkan Penjualan Pada UMKM Bakso Tusuk di Kota Bengkulu - Febliansa, M. Rahman; Soleh, Ahmad; Nova, Dwi; Maharani, Ririn Puspa (Jurnal Dehasen Mengabdi, 2025)
Growing micro, small and medium enterprises (MSMEs) in Bengkulu City, especially the bakso tusuk business, face obstacles when it comes to traditional marketing due to its limited reach. Social media can help businesses increase visibility and sales, but many businesses have yet to utilize it properly. The purpose of this study is to gather various strategies to utilize social media to increase sales of bakso tusuk. These strategies are intended to be inexpensive and effective. Socialization, training, and mentoring to bakso tusuk MSME players in Bengkulu City were used, focusing on platforms such as Instagram, Facebook, and TikTok. The results show that businesses have gained a better understanding of how to manage promotional content, interact with customers, and use simple analytics to measure the effectiveness of digital campaigns. It is expected that this socialization will increase sales and expand the market share of bakso tusuk in Bengkulu City. These results can be used as an example by other culinary MSMEs in using social media as a contemporary marketing tool.